2006
DOI: 10.1021/jf060178q
|View full text |Cite
|
Sign up to set email alerts
|

Salt-Induced Changes in Pork Myofibrillar Tissue Investigated by FT-IR Microspectroscopy and Light Microscopy

Abstract: FT-IR microspectroscopy and light microscopy were used to investigate pork muscle musculus semitendinosus samples, taken from three animals, that were subjected to brine salting at different concentrations (0.9, 3, 6, and 9% NaCl). Differences in spectral characteristics and in microstructure were observed in meat from animals differing in initial pH and varying salt concentrations. The FT-IR data displayed changes in the amide I region from 1700 to 1600 cm(-1). This spectral range was analyzed by principal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
47
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(60 citation statements)
references
References 45 publications
13
47
0
Order By: Relevance
“…For OLA-MP, increasing addition of OLA caused continuous decrease of amino acid side, resulting in a significant decrease in arginine. Band at 1639 cm −1 is an indicator for tightly bound water [30]. As can be seen, increasing addition of OLA caused a continuous increase of bound water in percentage, consistent with the increase in WHC (Fig.…”
Section: Ftirsupporting
confidence: 75%
“…For OLA-MP, increasing addition of OLA caused continuous decrease of amino acid side, resulting in a significant decrease in arginine. Band at 1639 cm −1 is an indicator for tightly bound water [30]. As can be seen, increasing addition of OLA caused a continuous increase of bound water in percentage, consistent with the increase in WHC (Fig.…”
Section: Ftirsupporting
confidence: 75%
“…Ten bands were determined, similar to the previous studies (B€ ocker, Ofstad, Bertram, Egelandsdal, & Kohler, 2006;Sun, Zhou, Sun, & Zhao, 2012;Zhou, Zhao, Su, et al, 2014). Amount of each secondary structural element given in percentage terms of the control and oxidized MPs are specifically shown in Table 1.…”
Section: Ftirmentioning
confidence: 79%
“…The protein secondary structural changes observed upon heating (increase in b-sheet structure) are consistent with literature references (Bouraoui et al, 1997;Moosavi-Nasab, All, Ismail, & Ngadi, 2005;Sánchez-González et al, 2008;Herrero et al, 2008b). In this connection, FT-IR spectroscopic studies in meat myofibrillar proteins have shown that the levels of b-sheet structures increase upon heating (Wang & Smith, 1994;Kirschner, Ofstad, Skarpeid, Hp~st, & Kohler, 2004;Böcker, Ofstad, Bertram, Egelandsdal, & Kohler, 2006;Wu et al, 2006;Wu, Bertram, Böcker, Ofstad, & Kohler, 2007). In myofibrillar proteins, complete protein denaturation and aggregation upon heat- 1.…”
Section: Raman Spectroscopic Analysismentioning
confidence: 99%